2019
DOI: 10.9734/jammr/2019/v30i1030243
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Pediatric Cancer Patients

Abstract: Background: In recent years the survival rates for children diagnosed with cancer has increased as result of successful treatment. Evaluation of health related quality of life during the process of treatments is important for recognition of acute dysfunction related to therapy and disease. Aim: Aim of the study is to identify the health-related quality of life in pediatric cancer patients and to detect the potential predictors of a total quality of life and its domains. Materials and Methods: It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
5
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
(33 reference statements)
5
5
2
6
Order By: Relevance
“…Using a large all-Saudi cohort and a wider range of ages, our data was able to confirm the results of Hegazy et al 16 regarding total HRQOL. In addition, we explain and discuss simple ways to improve QOL based on the results of our study.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Using a large all-Saudi cohort and a wider range of ages, our data was able to confirm the results of Hegazy et al 16 regarding total HRQOL. In addition, we explain and discuss simple ways to improve QOL based on the results of our study.…”
Section: Discussionsupporting
confidence: 87%
“…Our use of the parent proxy report PedsQL™ 3.0 cancer module is similar to a previous study from Saudi Arabia that obtained a total HRQOL of 72.3 for pediatric cancer patients, which was one of the of highest scores in the world (Table 4). [12][13][14][15][16] Of the 8 subscales, communication and procedural anxiety had the highest and lowest scores, respectively (Table 2). Similar to our data, other studies reported most frequent high scores for the communication subscale and most frequent low scores for procedural anxiety (Table 4), emphasizing the importance of these 2 subscales.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the decrease in their emotional functioning can be explained by the cultural difference in gender roles, as in Arabic culture, males -even children -are expected not to express emotions during stressful times and are expected to take more responsibility, which can eventually lead to psychological distress. This was conforming with a study conducted by Hegazy et al (35) who found that males experience more pain than females and a study by Liang et al (29) who found that men scored higher than women on the negative coping scales. On the other hand, a study done in Egypt found lower quality of life in female gender among children with cancer.…”
Section: Discussionsupporting
confidence: 91%